Teaching Methodology of Organic Chemistry in The 10th Classes of Specialized Schools on The Basis of Variative Curriculum - Ihtiyarova Gulnora Akmalovna; Hamidullayev Fatkhulla Lutfullayevich (Scientific Trends, 2023)
In this article, the procedure for organizing competitive classes based on a variable curriculum in the 10-11th grades of specialized schools, the types of competitive classes and the organization of lesson processes in them, to further increase the level of education of young people, and to provide comprehensive knowledge by uniting them for certain goals. The essence is explained. Also, to organize a selection class in the variable curriculum, to create study plans in groups with in-depth study of natural sciences, especially chemistry, to prepare special textbooks for them, to organize chemistry with modern methods, to teach each lesson based on laboratory experiments. it is thought that the transition will have a good effect on the students' mastery of natural sciences and continuing their studies for higher education.
Keywords: variable, innovative, selective class, interest, creativity, development, methodology, complex groups, variable curriculum, ability.